INCREASING ENTREPRENEURIAL MOTIVATION AND CREATIVITY AMONG GEN-Z IN CIREBON CITY TOWARDS ENTREPRENEURIAL INTEREST - Nillatica Aprilian Sismadewi; Vina Fidiyani; Anna Suzana; Sandi Nasrudin Wibowo (JURNAL ECONOMICA : Research of Economic And Economic Education, 2025)
The main objective of this study is to determine entrepreneurial motivation and creativity among Gen-Z as an interest in entrepreneurship. This research was designed using a quantitative descriptive approach. Data in the study were obtained from 293 respondents who are Gen-Z in Cirebon City. Data collection was obtained through a survey method using a questionnaire instrument with a Likert scale. Data analysis conducted in this study using the SEM PLS 4.0 test tool which includes testing discriminate validity, convergent validity, composite reliability, outer model, inner model and hypothesis testing. The results in this study indicate that: (1) Motivation has a positive and significant effect on entrepreneurial interest, (2) Entrepreneurial Creativity variables have a positive and significant effect on entrepreneurial interest, and (3) Motivation and Entrepreneurial Creativity have a positive and significant effect on entrepreneurial interest.